2021
DOI: 10.3389/fpls.2021.618245
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Diversity and Population Structure of Orobanche foetida Populations From Tunisia Using RADseq

Abstract: Orobanche foetida Poiret is a holoparasitic plant that lacks chlorophyll and totally depending on its host for its growth. Orobanche foetida parasitizes host plant roots and extract nutrient and water via a haustorium. Although O. foetida distributes in the Mediterranean region as a wild plant parasite, it parasitizes faba bean causing serious damages which may reach 90% yield losses in Tunisia. Analysis of genetic diversity of the parasite is important to better understand its evolution and spread, remained l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The use of different analysis tools can verify the reliability of results ( Qi et al, 2015 ; Boukteb et al, 2021 ), and the adoption of a reference genome is known to greatly improve the performance of RAD-seq technologies ( Torkamaneh et al, 2016 ). Given that several genomes in the Magnoliaceae were available (BioProject ID PRJNA774088 , Dong et al, 2021 ; Yin et al, 2021 ), we adopted a reference guided approach to process the population genetics of Magnolia fistulosa using both the Stacks and ipyrad pipelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of different analysis tools can verify the reliability of results ( Qi et al, 2015 ; Boukteb et al, 2021 ), and the adoption of a reference genome is known to greatly improve the performance of RAD-seq technologies ( Torkamaneh et al, 2016 ). Given that several genomes in the Magnoliaceae were available (BioProject ID PRJNA774088 , Dong et al, 2021 ; Yin et al, 2021 ), we adopted a reference guided approach to process the population genetics of Magnolia fistulosa using both the Stacks and ipyrad pipelines.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with traditional RAD-seq, double digest RAD sequencing (ddRAD-seq) further improves efficiency and robustness while minimizing cost ( Peterson et al, 2012 ). However, several studies have shown that the choice of pipeline used for the analysis may have a significant impact on the accuracy of the results ( Qi et al, 2015 ; Torkamaneh et al, 2016 ; Boukteb et al, 2021 ). To improve the reliability of the results, multi-method analyses can be adopted to process data using different technical routes ( Qi et al, 2015 ; Boukteb et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, evidence of host differentiation has been found in other parasitic weeds, such as O . foetida (Román, Satovic, et al, 2007 ; Román, Hernández, et al, 2007 ; Vaz Patto et al, 2008 , Thorogood et al, 2008 ; but not Boukteb et al, 2021 ), Striga hermonthica (Unachukwu et al, 2017 ), and Phelipanche ramosa (Stojanova et al, 2019 ). These differences may be due to specific methods/sampling design or may arise from the type of genetic marker selected as single locus co‐dominant markers are more efficacious for population biology insights (Sunnucks, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Restriction site-associated DNA (RAD) is one of the most effective genotyping-by-sequencing (GBS) methods that allow for extensive SNP discovery on the genome level ( Davey et al, 2011 ; Sonah et al, 2013 ; Puritz et al, 2014 ). It has been widely applied in population genetics for numerous model and non-model species (e.g., Wang et al, 2013 ; Luo et al, 2019 ; Feng et al, 2020 ; Xiong et al, 2020 ; Boukteb et al, 2021 ; Qiao et al, 2021 ). In particular, the UGbS-Flex (also denoted as SuperGBS) is a powerful tool for population genetic research with the ability to generate long reads (300–700 bp) and maximize SNP callings irrespective of the species ploidy level, breeding system, and reference genome availability ( Qi et al, 2018 ; Cheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%